The equation of the polynomial function is f(x) = (x + 4)(x -2)(x -9)(x + 2)(x + 2)(x + 2)
The given parameters are:
The polynomial function is represented as:
f(x) = n * (x - root)^multiplicity
So, we have:
f(x) = 1 *(x + 4)^1 * (x -2)^1 * (x -9)^1 * (x + 2)^3
This gives
f(x) = (x + 4)(x -2)(x -9)(x + 2)(x + 2)(x + 2)
Hence, the equation of the polynomial function is f(x) = (x + 4)(x -2)(x -9)(x + 2)(x + 2)(x + 2)
Read more about polynomial functions at:
https://brainly.com/question/2833285
#SPJ4